The characteristics of patients with multiple myeloma surviving over 10 years - Beihui Huang; Hongning Zhang; Junru Liu; Jingli Gu; Meilan Chen; Lifen Kuang; Xiaozhe Li; Juan Li (Frontiers in Oncology)
ObjectiveTo explore the characteristics of patients with multiple myeloma (MM) who have achieved long-term survival of over 10 years in the context where novel agents and autologous stem cell transplantation (ASCT) serve as the primary therapeutic modalities.MethodsA retrospective analysis was conducted on 168 MM patients diagnosed and treated in our institution from January 2004 to January 2014. 44 patients with a survival period exceeding 10 years were categorized into the long-term survival group, while 124 patients with a survival period of less than 10 years were categorized into the non-long-term survival group.ResultsBeing younger than 57 years old (OR 3.634, 95%CI 1.302-10.143), having a neutrophil count of at least 3.66 * 109/L (OR 3.122, 95% CI 1.093-8.918), absence of high-risk genetic abnormalities (OR 7.146, 95%CI 1.066-47.904), and receiving frontline ASCT (OR 4.225, 95%CI 1.000-17.841) were positively associated with a survival period exceeding 10 years in patients with MM. Achieving sustained minimal residual disease (MRD) negativity for at least 24 months is associated with long-term survival regardless of the presence of high-risk cytogenetic abnormalities.ConclusionBeing younger, having a neutrophil count above 3.66 * 109/L, the absence of high-risk cytogenetic abnormalities, and receiving frontline ASCT are independent protective factors for transplant-eligible MM patients to survive more than 10 years. Achieving maintained MRD negativity status for over 24 months might be associated with long-term survival.